The Relationship Between Characteristics and Knowledge Of Pharmaceutical Engineering Personnel In Reconstitution Of Antibiotic Injection At RS UNS Inpatients - Septiyani Dwi Utari (SEKOLAH TINGGI ILMU KESEHATAN NASIONAL, 2022)
Reconstitution is the process of mixing the solvent medium into a dry powder mass to produce suspended or dissolved substances. Mixing injection drugs, including reconstitution of antibiotic injections, should be formulated by pharmacists, in fact all of them are still made by non-pharmaceutical health workers, apart from lack of correlation, it also gives the impression that the hospital is violating the rules. To prevent errors in compounding, pharmaceutical staff attend aseptic technique training to minimize contamination during compounding. The purpose of this study was to examine the relationship between characteristics and knowledge of pharmaceutical technicians in reconstitution of antibiotic injections at UNS Hospital inpatients. Descriptive research with correlation studies the relationship between two or more variables. Data collection is done.total.sampling. Retrieval of data used a questionnaire and processed with SPSS 21.0 For.Windows application. The results of this study indicate that the characteristics include gender, p value = 0.014, at = 0.05 (p<α), education p value = 0.961, at = 0.05 (p>α), length of work p value = 0.719, at =0.05 (p>α). The conclusion obtained is that there is no significant relationship between education and length of work. There is a significant relationship between gender in the knowledge of pharmaceutical technicians in reconstitution of antibiotic injections at UNS Hospital inpatients.